Penerapan Metode EXPROM II Dalam Menentukan Tempat Wisata Pantai Terbaik - Mesran Mesran; Agung Triayudi; Dini Nofrisa; Rizkah Fadillah (Universitas Budi Darma, 2023)
Tourism is an activity or activity carried out by humans in order to find pleasure or provide space for themselves to rest themselves from daily fatigue. The word tourism describes the expression of pleasure for someone who will enjoy a holiday by going somewhere. Many beaches in Indonesia in various regions make people confused in choosing which place to visit while on vacation. To assist visitors in choosing which beaches should be visited, a system is needed. A good system used in this problem is a decision support system. A decision support system is a system that has the same working procedures as a computer system. DSS requires a method. The method used in this study is the EXPORM II method. The EXPORM II method is a modified method of the PROMITHE II method. Where the EXPORM II method is easier than the PROMITHE II method. However, it has the same accurate results as the PROMITHE ll method. The results of this study are that the best alternative is Cemara Kembar Beach as an alternative to A7 with a value of 0.69889 which in the end is suggested to be the best beach resort.